Modernisasi Agama Di Indonesia - Syah, Irman; Amalia, Putri; Anugrah, Anugrah (Jompa Research and Development, 2025)
This article discusses the diverse concept of moderation in various contexts, from its definition and basic values ​​to its implementation in Indonesia. Moderation, which comes from the Latin